The Effect of Using Flashcards on Preschool Children's Language Development - Fadhilah, Umu; Tami, Putri Denanda; Sari, Komala; Arianingsih, Tri; Wati, Liza (J-LELC: Journal of Language Education, Linguistics, and Culture, 2025)
Preschool education is a vital part of producing a quality generation, and language is a crucial component of the child development process. Flashcard media is one of the media used for children's vocabulary and language acquisition. undefined to find out the effect of using flashcard media on preschool children's language development.  This study used a Pre-Experimental research design with One one-group pretest post-test design. The samples were 20 PAUD students Mulya Baran Barat. Data analysis using non-parametric statistical tests, namely the Wilcoxon test. The results stated that most respondents (65%) were in the age range of 4 years and female gender (65%). While the ability before research using flashcard media was mostly (65%) and after research using flashcard media language development increased by as much as (75%). So the results of the analysis obtained a P- value of 0.00, meaning that there is an effect of using flascard media on the language development of preschool children at PAUD Mulya Baran Barat.